Chapter The origins of the putting-out or domestic system of industrial production in England - Amor, Nicholas R. (Datini Studies in Economic History, 2023)
The putting-out system of production was a key feature of England's woollen cloth industry and is regarded by many historians as a step along the road to capitalism. This paper considers the evolution of the industry in the late Middle Ages, the emergence of clothiers and their dependent out-workers and the nature of the relationship between the two groups. A detailed analysis follows of the growth, between 1475 and 1510, in the value of textile related debt litigation in the Court of Common Pleas, and revised estimates are given for the scale of the industry and the size of the workforce in the early-sixteenth century. Thus an assessment can be made of the importance of the putting-out system and its contribution to the success of the textile industry at that time.